Atypical Serogroup IVb-v1 of Listeria monocytogenes Assigned to New ST2801, Widely Spread and Persistent in the Environment of a Pork-Meat Producing Plant of Central Italy - Guidi, Fabrizia; Lorenzetti, Cinzia; Centorotola, Gabriella; Torresi, Marina; Cammà, Cesare; Chiaverini, Alexandra; Pomilio, Francesco; Blasi, Giuliana (Frontiers in Microbiology, 2022)
In this study, we characterized 84 Listeria monocytogenes (Lm) strains having an atypical IVb-v1 serogroup profile and assigned to the new MLST type ST2801 (CC218), isolated in a meat producing plant of Central Italy. The new ST was widespread in the food producing environment where it was able to persist over a year even after cleaning and sanitation. Cluster analysis identified three main clusters genetically close to each other (0-22 allelic differences, 0-28 SNPs) from two different cgMLST types, suggesting a common source. The coexistence of closely related clusters over the time could be the result of a different evolution path starting from a common ancestor firstly introduced in the plant and/or the repetitive reintroduction of closely related clones probably by raw materials. All the strains presented several determinants for heavy metals resistance, stress response and multi-drugs efflux pumps with no significant differences among the clusters. Fifty-three strains carried pLI100 and the j1776 plasmids while in one strain the pLM33 was found in addition to pLI100. Only the strains carrying plasmids presented cadA and cadC for cadmium resistance, the mco gene encoding a multicopper oxidase and gerN for an additional Na+/H+-K+ antiporter. All the strains presented a virulence profile including a full length inlA gene and the additional LIPI-3. The isolation of a new ST with a large pattern of stress-adaptation genes and able to persist, is an important contribution to deepen the current knowledge on the uncommon IVb-v1 and in general on genomic diversity of Lm.